In Vitro susceptibility of Gram-positive cocci isolated from skin and respiratory tract to azithromycin and twelve other antimicrobial agents - Mendes,Caio M. F. (2001)
This study was conducted to evaluate the activity of azithromycin in comparison to 12 other antibacterial agents against recent isolates obtained consecutively from patients with respiratory tract or skin infections, from January to July, 2000. A total of 717 Gram-positive cocci were analyzed in this study and the following species were studied: Staphylococcus aureus (n=576), beta-hemolytic streptococci ( n=115), and Streptococcus pneumoniae (n=26). Susceptibility testing was carried out by the disk diffusion method and interpreted according to NCCLS breakpoints. The activity of azithromycin was compared to erythromycin, clindamycin, chloramphenicol, ciprofloxacin, ofloxacin, oxacillin, penicillin, ceftriaxone, tetracycline, trimethoprim/sulfamethoxazole, teicoplanin, and vancomycin. Of the 26 S. pneumoniae isolates recovered from the respiratory tract, 5 (19.2%) were intermediate resistant to penicillin. All of these strains were susceptible to chloramphenicol, ofloxacin, and vancomycin, and 24 (92%) were also susceptible to azithromycin, clindamycin, and erythromycin. Among the 67 beta-hemolytic streptococci strains isolated from the respiratory tract, 66 (99%) were susceptible to azithromycin, erythromycin, clindamycin, and ofloxacin. All 48 beta-hemolytic streptococci strains isolated from skin were susceptible to azithromycin and clindamycin, 47 (98%) were susceptible to erythromycin, and 46 (96%) were susceptible to ofloxacin. Of the 576 strains of S. aureus, 253 (43.9%) were isolated from the respiratory tract and 323 (56.1%) from skin. Among S. aureus isolates from the respiratory tract and skin, 46 (18%) and 78 (24%), respectively were resistant to oxacillin. Isolates from the respiratory tract and skin showed the same percentage of resistance (36%) to azithromycin. These in vitro results suggest that azithromycin can be a therapeutic option for treatment of infections caused by these bacteria since the newer macrolides have several distinct advantages over erytromycin including improved oral bioavailability, longer half-life allowing once or twice daily administration, higher tissue concentrations and less gastrointestinal adverse effects.